LEBIH DARI SEKEDAR DISIPLIN : CONSCIENTIOUSNESS DAN RESILIENSI PADA MAHASISWA - Alda Varida; Amira Naila Rizqia; Rezzy Tikaso; Nadya Maya Kamiliya Ramdan; Noura Salma Aisyadila; Aisya Nisrina Zahra; Sri Maslihah (Universitas Mercu Buana, 2025)
This study investigated the association between conscientiousness and resilience among Indonesian university students. Using a cross-sectional correlational design, data were collected from 307 students enrolled in public and private universities in Indonesia. Conscientiousness was measured using the International Personality Item Pool (IPIP) Conscientiousness Scale, and resilience was assessed using the Connor–Davidson Resilience Scale (CD-RISC). Spearman correlation analysis revealed a significant positive association between conscientiousness and resilience (rₛ = .249, p < .01). The findings indicate that students characterized by greater self-discipline, responsibility, and goal orientation tend to exhibit higher levels of resilience. Although the association was modest in magnitude, the results support personality-based models of resilience and suggest that conscientiousness represents one of multiple factors contributing to adaptive functioning in emerging adulthood. Interventions aimed at strengthening self-regulatory capacities may therefore complement resilience-building efforts within higher education settings. Longitudinal studies are needed to examine causal pathways and identify additional determinants of resilience among university students.